2021
DOI: 10.1111/scs.13038
|View full text |Cite
|
Sign up to set email alerts
|

Dignity reflections based on experiences of end‐of‐life care during the first wave of the COVID‐19 pandemic: A qualitative inquiry among bereaved relatives in the Netherlands (the CO‐LIVE study)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Such experiences were often described as traumatic, and accompanied by feelings of sadness, guilt, anxiety and feeling ‘cheated’. 1 , 13 High levels of loneliness, social isolation and emotional support needs have also been observed among bereaved participants in this study, in conjunction with difficulties accessing both informal and formal sources of bereavement support. 5 , 16 …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Such experiences were often described as traumatic, and accompanied by feelings of sadness, guilt, anxiety and feeling ‘cheated’. 1 , 13 High levels of loneliness, social isolation and emotional support needs have also been observed among bereaved participants in this study, in conjunction with difficulties accessing both informal and formal sources of bereavement support. 5 , 16 …”
Section: Introductionsupporting
confidence: 59%
“… 12 Quantitative and qualitative studies have identified difficult experiences of end-of-life care, such as lack of communication and contact with healthcare staff and patients prior to the death. 1 , 13 16 Where bereaved people struggled to make sense of such experiences, ‘disrupted meaning’ was found to cause functional impairment and dysfunctional grief symptoms. 12 The distress caused to family members by visiting restrictions, missed opportunities to spend time with and say goodbye to their dying family member, and feelings of frustration at poor communication from healthcare staff is documented in the qualitative results of one of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the total number of 28 studies, 16 articles reported qualitative data ( Becqué et al, 2021 ; Borghi & Menichetti, 2021 ; Cardoso et al, 2020 ; De Leon Corona et al, 2021 ; Guité-Verret et al, 2021 ; Hamid & Jahangir, 2020 ; Helton et al, 2020 ; Hernández-Fernández & Meneses-Falcón, 2021 ; Kentish-Barnes et al, 2021 ; Menichetti Delor et al, 2021 ; Mohammadi et al, 2021 ; Moore et al, 2020 ; Mortazavi et al, 2021 ; Motamedzadeh et al, 2021 ; Selman et al., 2021 ; Testoni et al, 2021 ), 10 articles were quantitative studies ( Carson et al, 2021 ; Chen & Tang, 2021 ; Eisma & Tamminga, 2020 ; Eisma et al, 2021 ; Lee et al, 2021 ; Schloesser et al, 2021 ; Şimşek Arslan & Buldukoğlu, 2021 ; Tang & Xiang, 2021 ; Wang et al, 2021 ), and two articles had a mixed-methods design ( Harrop et al, 2021 ; Mayland et al, 2021 ). An overview of the included studies is provided in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore vital that health professionals are clearly aware of the possibilities for family caregivers to be there. The European Respiratory Society also recommends that family caregivers be allowed to visit dying patients despite the infection risk (Janssen et al, 2020 ) and recent studies of bereaved relatives highlight this issue (Becqué et al, 2021 ; Guité-Verret et al, 2021 ; Hanna et al, 2021 ). Furthermore, visiting regulations must be communicated clearly and be easy to understand (Hart et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%